Perspectives on Rebuilding Health System Governance in Opposition-Controlled Syria: A Qualitative Study - Yazan Douedari; Natasha Howard (Kerman University of Medical Sciences, 2019)
Background Ongoing conflict and systematic targeting of health facilities and personnel by the Syrian regime in opposition-controlled areas have contributed to health system and governance mechanisms collapse. Health directorates (HDs) were established in opposition-held areas in 2014 by the interim (opposition) Ministry of Health (MoH), to meet emerging needs. As the local health authorities responsible for health system governance in opposition-controlled areas in Syria, they face many challenges. This study explores ongoing health system governance efforts in 5 opposition-controlled areas in Syria.   Methods A qualitative study design was selected, using in-depth key informant interviews with 20 participants purposely sampled from HDs, non-governmental organisations (NGOs), donors, and service-users. Data were analysed thematically.   Results Health system governance elements (ie, strategic vision, participation, transparency, responsiveness, equity, effectiveness, accountability, information) were considered important, but not interpreted or addressed equally in opposition-controlled areas. Participants identified HDs as primarily responsible for health system governance in opposition-controlled areas. Main health system governance challenges identified were security (eg, targeting of health facilities and personnel), funding, and capacity. Suggested solutions included supporting HDs, addressing health-worker loss, and improving coordination.   Conclusion Rebuilding health system governance in opposition-controlled areas in Syria is already progressing, despite ongoing conflict. Local health authorities need support to overcome identified challenges and build sustainable health system governance mechanisms.